If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -6x = 14 + -7x Solving -8 + -6x = 14 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -8 + -6x + 7x = 14 + -7x + 7x Combine like terms: -6x + 7x = 1x -8 + 1x = 14 + -7x + 7x Combine like terms: -7x + 7x = 0 -8 + 1x = 14 + 0 -8 + 1x = 14 Add '8' to each side of the equation. -8 + 8 + 1x = 14 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = 14 + 8 1x = 14 + 8 Combine like terms: 14 + 8 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| 52=4(-2x+3) | | -2x+5y=-54 | | 2x(x-3)(x-2)= | | 5-4x-3=-4 | | 3h+2c+f=19 | | -3(2x+4)=24 | | -4(x-2)+x=-4 | | 5x+3-2x=3x+10 | | 348.16+16.96+11.01=y | | 9=-9-2x | | 3x(x+2)(x+4)= | | 51=-3x | | -4x-42=-10 | | 3ex-4+8=10 | | -3(4-2x)+4x=x-21 | | 5(w+3)-(4w+5)=5 | | 7(r-5)(4r-1)=0 | | 66.64+7.42+11.01=y | | 38y+15y+22y+6y+44y+5y= | | 0x=76 | | -11+3x=-(2x-3)-4 | | -9x+76=-32-3x | | 2X*(2X+2)=624 | | 10x^4+19x^3+7X^2=0 | | -18x-6(-0.5)=-33 | | -16+x=5(2-5x) | | -x^4-x^2+6=0 | | -3X^2+24X-9=0 | | 6x^2-3x-84=0 | | (4x-3)-6=31 | | -4x-2y=30 | | 15-3(2m-4)=9 |